The role the university could play in an inclusive regional innovation system - Wei Yao; Heng Li; Mosi Weng (Triple Helix, 2018)
Extant research shows that universities do not usually foster an inclusive innovation system. This paper examines an innovation program at Zhejiang University that targeted rural areas in China, and that sought to promote an inclusive innovation system. This case illuminates how universities could play a critical role in configuring inclusive regional innovation systems by means of selection, improvement and diffusion of technology, dissemination and absorption of knowledge, access to science and technology, intermediation between the actors of innovation, training skilled labor, and cultivating talent. We underscore how the inclusive innovation program of Zhejiang University allowed this university to help realize the enormous consumption, production, and entrepreneurial potential of low-income households in rural China.
Keywords: 330; Inclusive innovation; University